A Comprehensive Review on the Synthesis and Energy Applications of Nano-structured Metal Nitrides - Ashraf, Iffat; Rizwan, Syed; Iqbal, Mudassir (Frontiers in Materials, 2020)
Nanosized metal nitrides due to their chemical characteristics which make them sustainable alternatives to noble metals in catalysis have drawn the attention of researchersworldwide. Transition metal nitrides are very similar in their method of synthesis, properties and applications. Their synthetic parameters are considered to be main factor for determining effectiveness of metal nitrides in photocatalysis, energy storage devices,remediation of environmental pollutants, gas sensors and biomedical applications. This review focusesonvery recent advancesfor synthetic approaches and electrocatalytic applications ofmetalnitrides. The synthetic approaches will provide an overview of cost of production, consumption of energy and timerequired for synthesis. Furthermore some of recent techniques such as electrochemical, sol-gel,solvothermal, sonochemical, solid-state reaction, chemical synthesis and many more techniques that offer new path for researchers are also discussed. Various applications in electrocatalysis, water splitting, lithium ion batteries,and super-capacitors etc are summarized. We are pretty confident that this review willprovidevery useful information for the upcoming community of researchers, interested insynthesizing nitrides for various applications.